Real‐world experience with the new Watchman FLX device: Data from two high‐volume Sicilian centers. The FLX‐iEST registry. Issue 1 (20th May 2022) - Vizzari, Giampiero; Grasso, Carmelo; Sardone, Andrea; Mazzone, Paolo; Laterra, Giulia; Frazzetto, Marco; Sacchetta, Giorgio; Micari, Antonio; Tamburino, Corrado; Contarini, Marco
Abstract: Introduction: The Watchman‐FLX left atrial appendage closure (LAAC) device presents innovative features: higher conformability, reduced length, closed distal "flex‐ball" during deployment, and flattened surface. We report our real‐world experience with the Watchman‐FLX device in two centers with consolidated LAAC expertise. Methods: We enrolled 200 consecutive Watchman‐FLX patients (2019–2021) in a nonrandomized double‐center registry; procedural data and follow‐up for midterm clinical outcomes were collected. A control group of 100 patients treated with first‐generation Watchman (2.5) was included. Results: According to mean CHAD2 DS2 ‐VASc (5 ± 1.40) and HAS‐BLED (3.8 ± 1.01) scores, the population included in this study was at high risk: 29% had a previous stroke and 56.5% a bleeding event. Main LAAC indications were symptomatic hemorrhage (39.5%), need for triple antithrombotic therapy (39%), gastrointestinal bleeding (32%), and oral anticoagulation intolerance (18%). Transesophageal echocardiography guidance was followed in 93% of cases (48% in general anesthesia and 45% under conscious sedation). Repositioning an FLX device was required in 20% of cases and no complication occurred. In 96% of patients, the first selected device was delivered, while in 4% a device size change was required after the first choice (7% with Watchman 2.5). Peridevice leaks (<5 mm) were found postimplant in two cases (1%). Overall, the procedural success rate was 99.5%. One patient's procedure was unsuccessful (0.5%), due to left atrial appendage (LAA) anatomy; differently, the mean failure rate with Watchman 2.5 was 2%. No device embolization was reported. Complications (8.5%) were mainly related to the access site (3%); major bleedings (1%), and in‐hospital death (0.5%) rarely occurred. After a follow‐up of 272 ± 173 days, 2.3% of cases experienced a non‐device‐related stroke and 0.6% fatal bleeding. Conclusion: Our registry showed a high procedural success rate of the Watchman‐FLX in a high‐risk population. According to our experience, the main advantages include easy implanting and repositioning, absence of embolization, good LAA sealing, and low rate of complications in the follow‐up period.